2013
DOI: 10.1007/s11420-013-9328-x
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Navigation in Patellofemoral Arthroplasty: a New Technique to Improve Rotational Position of the Trochlea

Abstract: The short-term results suggest that navigation can lead to better trochlear rotation which, in our hands, is associated with fewer cases of patellar maltracking and better overall clinical scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
0
11
1
Order By: Relevance
“…24,25 Prior literature also suggests that computer navigation improves trochlear rotation in PFA, and smaller studies of robotic-arm-assisted BKA have shown good results. 18,23 In this study, we did not find that improved revision rates after CA partial knee arthroplasty persisted at the 2-year time point.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…24,25 Prior literature also suggests that computer navigation improves trochlear rotation in PFA, and smaller studies of robotic-arm-assisted BKA have shown good results. 18,23 In this study, we did not find that improved revision rates after CA partial knee arthroplasty persisted at the 2-year time point.…”
Section: Discussioncontrasting
confidence: 62%
“…19,20 The most consistently described benefit of computer assistance in knee arthroplasty is improved implant position and accurate alignment. [21][22][23] For UKA specifically, low-volume surgeons have higher revision rates, and robotics reduce revision and improve alignment in the hands of these surgeons. 24,25 Prior literature also suggests that computer navigation improves trochlear rotation in PFA, and smaller studies of robotic-arm-assisted BKA have shown good results.…”
Section: Discussionmentioning
confidence: 99%
“…65 showed that navigation was a safe and reliable method to obtain correct implant correction with the Avon implant. Hernigou et al replicated these findings, showing no maltracking in the navigated group in their study 66 .…”
Section: Surgical Techniquementioning
confidence: 69%
“…Current designs use more sophisticated guiding instruments that mostly refer to the intramedullary femoral canal, anterior cortex, mechanical tibial axis, femoral epicondyles, direction of the native trochlea or a combination of these. Some authors remind us of the added value of navigation [10]. Most PFAs are based on TKA trochlea templates and anterior femoral cuts (Bonlay^) or sinking the trochlea shield into the native trochlea (Binlay^).…”
Section: Discussionmentioning
confidence: 99%